2023
DOI: 10.1002/pmrj.13002
|View full text |Cite
|
Sign up to set email alerts
|

Physical therapist–led interventions based on the biopsychosocial model provide improvement in disability and pain for spinal disorders: A systematic review and meta‐analysis

Abstract: ObjectiveTo summarize the effects of physical therapist–led interventions based on the biopsychosocial (BPS) model in spinal disorders compared to interventions with no BPS model through a systematic review and meta‐analysis of randomized‐controlled trials.TypeSystematic review and meta‐analysis.Literature SurveyWe searched the Web of Science, CENTRAL, MEDLINE, PsycINFO, CINAHL, and PEDro up to October 27, 2022.MethodologyPain intensity and disability were primary outcomes and psychological factors were second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 84 publications
(163 reference statements)
0
2
0
Order By: Relevance
“…Therefore, it is relevant to determine cost-effective therapeutic strategies that can improve the clinical condition of patients. In this sense, therapeutic strategies directed by physical therapists based on the biopsychosocial (BPS) model have been shown to effectively improve symptoms in people with spinal disorders ( Miki et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is relevant to determine cost-effective therapeutic strategies that can improve the clinical condition of patients. In this sense, therapeutic strategies directed by physical therapists based on the biopsychosocial (BPS) model have been shown to effectively improve symptoms in people with spinal disorders ( Miki et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic low back pain (cLBP) is not only a health problem, but a social concern [ 27 ]. Notably, its substantial impact on healthcare expenses, work absenteeism, and diminished productivity can severely impact a nation’s economy [ 28 ]. Furthermore, a paradox arises from the fact that such a prevalent, significant, and widespread condition such as chronic cLBP is characterized by diverse and occasionally conflicting treatment guidelines, leading to confusion among both patients and pain therapists.…”
Section: Perspectivesmentioning
confidence: 99%
“…People with persistent, non-specific spinal pain who also have psychosocial risk factors associated with the development or maintenance of persistent pain, are often treated by physiotherapists ( Synnott et al, 2015 ). The use of a biopsychosocial model, an approach within healthcare that acknowledges health and illness result from complex interactions between biological, psychological, and social factors ( Engel, 1977 ), is advocated in the physiotherapy pain management of these people ( Hartvigsen et al, 2022 ; Ho et al, 2022 ; Miki et al, 2023 ). However, physiotherapists indicated that they do not always have the necessary skills and confidence to successfully address and treat the psychological problems seen in spinal pain ( Synnott et al, 2015 ; Holopainen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%